Implementasi Model Edukatif "Make A Match" Sebagai Strategi Layanan Bimbingan Kelompok Untuk Meningkatkan Keterampilan Sosial Siswa SMP - Siti Maisaroh; Sulistiyana Sulistiyana; Hendro Yulius Suryo Putro (JURNAL MANAJEMEN PENDIDIKAN, 2026)
IMPLEMENTATION OF THE "MAKE A MATCH" EDUCATIONAL MODEL AS A GROUP GUIDANCE SERVICE STRATEGY TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS' SOCIAL SKILLS This study aimed to improve the social skills of junior high school students through the implementation of the Make a Match educational model in group guidance services. The study employed a Guidance and Counseling Action Research (PTBK) design involving eight eighth-grade students with low social skills. The research was conducted in three cycles consisting of planning, action, observation, and reflection. Data were collected through observations, interviews, documentation, and social skills assessment instruments, and analyzed using descriptive analysis techniques. The results indicated that the implementation of the Make a Match educational model gradually improved students' activity and social skills. The average student activity increased from 65.94% (fair category) in Cycle I to 95.31% (very good category) in Cycle II and reached 98.75% (very good category) in Cycle III. Improvements were also found across all social skill indicators, including communication, cooperation, empathy, social participation, and self-control, supported by interview findings from the guidance and counseling teacher, homeroom teacher, and students, which confirmed positive changes in students' social behavior. These findings indicate that the Make a Match educational model is effective as a strategy in group guidance services to improve junior high school students' social skills. However, the study was limited by the small number of participants and its implementation in a single school, which restricts the generalizability of the findings.